TEMUAN RANGKA MANUSIA AUSTRONESIA DI PANTURA JAWA TENGAH: Â€ŒSEBUAH KAJIAN AWAL" - Gunadi Kasnowihardjo (Berkala Arkeologi, 2013)
Preliminary research in Lasem, Sluke and Kragan Districts, Rembang Regency, Central Java has been conducted in late 2012. The first problem in this study is to reviewing the Prehistoric Burials Site at North Beach area (PANTURA) of Rembang Regency. The objective is to seek possibility of discovering several prehistoric grave sites along the coast between Kragan and Lasem Districts. By surveying the surface along the coast, was found a few locations that are identified as prehistoric grave site such in the village of Leran, Sluke District and village of Binangun, Lasem District. Based on the survey results followed by excavation to learn more about the grave sites, especially the skeleton that was buried as the main data of this research. The skeleton findings those are typical of the Austronesian culture. This finding is significant data. Even in terms of paleoanthropological study known about tooth modification in some individuals, both of which are found on Binangun and Leran. Modified forms of the teeth look likes jasmine flower buds have never been found anywhere else in Indonesia.